Experimental and Theoretical Research on Valve Head Compensation for Nonlinear Characteristic of Evaporator - Zhang Chuan; Chen Jiangping; Chen Zhijiu; Chen Wenyong (Zhileng xuebao)
Through dividing electronic expansion valve from evaporator system and based on constant gain of superheat open loop rule, the compensation theory of valve head was analyzed. On the basis of compensation theory and the characteristic experiment results, a valve head was designed which has compensation function for evaporator nonlinear characteristic. Moreover, a series of comparison tests were performed. The result shows that the compensation valve head improved the control characteristic of electronic expansion valve and the superheat of the evaporator decreased.